Analisis modal kerja, current ratio, quick ratio dan cash ratio terhadap profitabilitas di Bursa Efek Indonesia - Melpa Gusparini; Handra Tipa (Owner : Riset dan Jurnal Akuntansi, 2022)
The amount of working capital and liquidity obtained by a company has a relationship with the profit figure achieved by a company as a result of its performance, but the working capital and liquidity figures are not a reference for profits that can be obtained by all companies in the food and beverage subsector. This study aims to analyze the effect of working capital, current ratio, quick ratio and cash ratio on profitability on the IDX. The research method used is quantitative consisting of 27 populations, with purposive sampling technique with the acquisition of a sample of 6 companies, based on field research data and literature studies and processed through SPSS 28 is the technique taken in this study in collecting all data. The results that have been studied are that there is no significant effect jointly between all dependent variables on the independent variable, namely profitability. The t-test of the current ratio and the quick ratio have a significant effect on profitability. In the other two dependent variables, namely working capital and cash ratio, the results show no significance.